Enhancing Energy Efficiency in Industrial Warehouses Using Life Cycle Cost Analysis (LCCA) - Pratama Jaya; Taufik Roni Sahroni (Advance Sustainable Science Engineering and Technology, 2025)
Industrial warehouses use inefficient lighting systems that occupy a significant portion of energy consumption and operating expenses. The aim of this study is to attain higher energy efficiency and reduce the lighting cost by replacing conventional high-pressure mercury vapor (HPL-N) lamps with LEDs in a warehouse environment. The study employs the Life Cycle Cost Analysis (LCCA) methodology to evaluate long-term cost-effectiveness and save energy. Data were collected using literature review, field surveys, and light simulation using Dialux software at PT XYZ warehouse in Cilegon, Indonesia, between January and June 2024. Findings reveal that the use of LED lighting, in conjunction with the optimization of the light point number, reduces energy consumption by 65%, saving 121,929.816 kWh of energy annually. Within 11 years, installation of LED saves an amount of Rp 947,683,204 compared to Rp 1,796,422,585 with HPL-N systems—an amount of 50.66% or Rp 848,739,381 saved. The results show the energy and economic benefits of the use of LED in industrial warehouses to be advantageous for national energy saving as well as satisfying light standards.